ANALISIS PENGARUH KOMPENSASI, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BPR NBP 20 DELITUA - Purba, Betniar (Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of compensation, training and work discipline on employee performance at PT BPR NBP 20 Delitua. Data was collected by distributing questionnaires to 36 respondens. From the results of the study obtained multiple regression equations as follows: Y = 1,484 + 0.262X1 + 0.174 X2+ 0,480 X3 . All regression coefficient is are positive, meaning that all independent variables, namely compensation, training and work discipline, have a positive effect on the dependent variable, namely employee performance. Of the three independent variables, work discipline has a greater influence on employee performance because it has largest regression coefficient 0,480. Based on partial hypothesis testing, compensation, training and work discipline have a significant effect on employee performance where the significance value of each variables is smaller than alpha (0,05). Based on simultaneous hypothesis testing, the three independent variables, namely compensation, training and work disciplinehave a significanteffect on the dependent variable, namely employee performance. This can be seen from the significance value of 0,000< alpha (0,05). The coefficient of determination ( R Square of 0,850 means that employee performance can be explained by compensation, training and work discipline of 0,85 % while the remaining 15,00 % is explained by other variables not explained in this study such as motivation, work conditions and competence. From the result of research and discussion, PT BPR NBP 20 Delitua should develop and maintain indicators of compensation, training and work discipline on employee performance at PT BPR NBP 20 Delitua.